Social Networks in Ghana - Christopher Udry; Timothy G. Conley (Yale University, Economic Growth Center, 2004)
In this chapter we examine social networks among farmers in a developing country. We use detailed data on economic activities and social interactions between people living in four study villages in Ghana. It is clear that economic development in this region is being shaped by the networks of information, capital and influence that permeate these communities. This chapter explores the determinants of these important economic networks. We first describe the patterns of information, capital, labor and land transaction connections that are apparent in these villages. We then discuss the interconnections between the various economic networks. We relate the functional economic networks to more fundamental social relationships between people in a reduced form analysis. Finally, we propose an equilibrium model of multi-dimensional network formation that can provide a foundation for further data collection and empirical research.
Keywords: O12; D85; 330; Endogenous Networks; Informal Credit; Social Learning; Landwirte; Informeller Finanzsektor; Ghana; Soziales Netzwerk